Predictive factors in breast cancer – the present and the future Current state of knowledge presented at the 2007 ASCO Meeting - Senkus-Konefka, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2007)
In spite of recent rapid development of anti-cancer drugs, including therapies targeted at specific molecular mechanisms of cancer initiation, progression and spread, many patients still receive treatments based on data relevant to average patient populations, and not to individual features of patients and their cancers. The progress of knowledge on molecular mechanisms of carcinogenesis and action of anti-cancer drugs will hopefully allow for better prediction of their therapeutic effect in individual patients. This may allow for selection of optimal, individualized active treatment and avoidance of ineffective, toxic therapies in patients with low probability of response. The possibility of treatment efficacy prediction also has obvious economic advantages. This review describes current knowledge on predictive factors in breast cancer, presented at the 2007 ASCO Meeting.